THE IMPLEMENTATION OF RUNNING DICTATION TO IMPROVE THE STUDENTâS LISTENING SKILL OF TENTH GRADE SCIENCE PROGRAM (X MIA4) IN SMA NEGERI 4 MALANG - Arifiana, Novi Dwi Pratista (Jurnal Pendidikan Saintifik, 2014)
English Department Faculty Of Teacher Training And Education University Of Muhammadiyah Malang     ABSTRACT: This study aims to describe the implementation of the Running Dictation in improving listening skills recount text MIA 4 class X students in SMAN 4 Malang. The design used for this study is the CAR (Classroom Action Research). This study uses two cycles at each cycle consisted of two meetings. From this study, it can be concluded that, Running Dictation proven to improve students listening skills recount text. Usually it is difficult to capture the students of the recording because the sound is not clear, accent difficult or the speaker is not clear. By using this technique, it can eliminate the drawbacks listen through the tape. In running dictation, students are required to memorize the word and tell their friends. That is, they not only learn the skills, but also four English skills. Running Dictation can be an alternative in teaching listening. It can help teachers to improve the teaching and learning process.  Keywords: Running Dictation, listening skills